2021
DOI: 10.21273/jashs05002-20
|View full text |Cite
|
Sign up to set email alerts
|

Far-red Fraction: An Improved Metric for Characterizing Phytochrome Effects on Morphology

Abstract: Phytochrome, a well-studied photoreceptor in plants, primarily absorbs in the red (R) and far-red (FR) regions and is responsible for the perception of shade and subsequent morphological responses. Experiments performed in controlled environments have widely used the R:FR ratio to simulate the natural environment and used phytochrome photoequilibrium (PPE) to simulate the activity of phytochrome. We review why PPE may be an unreliable metric, including differences in weighting factors, multiple phytochromes, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 112 publications
(196 reference statements)
1
27
0
Order By: Relevance
“… Kusuma and Bugbee (2021) recently outlined six issues with using PPE as a model to predict morphological responses. These included (1) differences in photoconversion coefficients from different studies, (2) multiple phytochromes, (3) thermal reversions, (4) phytochrome intermediates, (5) fluctuations in Ptotal, and (6) spectral distortion by chlorophyll.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Kusuma and Bugbee (2021) recently outlined six issues with using PPE as a model to predict morphological responses. These included (1) differences in photoconversion coefficients from different studies, (2) multiple phytochromes, (3) thermal reversions, (4) phytochrome intermediates, (5) fluctuations in Ptotal, and (6) spectral distortion by chlorophyll.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the issues with PPE outlines above, Kusuma and Bugbee (2021) suggested that environmental signals may be more reliable than photo-molecular models, like PPE. Environmental pressure drives evolution, and thus genetically regulated molecular machinery could be expected to conform to the incoming signals (in so much as it provides a survival advantage).…”
Section: Discussionmentioning
confidence: 99%
“…Sensors with red light/far-red light detection are becoming widely used (Kusuma and Bugbee, 2021). With the addition of a micro data logger (microCache, Apogee Instruments) featuring wireless connection to mobile devices, these sensors are easier to use.…”
Section: Chlorophyll Concn (Gámmentioning
confidence: 99%
“…Although P r and P fr are named for the region that they are most sensitive to, both forms absorb across the entire biologically active range of radiation (300 to 800 nm). Historically, a metric called phytochrome photoequilibrium (PPE) has been used to predict phytochrome-mediated developmental responses [2]. PPE is an estimate of the fraction of active P fr to the total phytochrome pool, and it is calculated from the spectral photon distribution (SPD) of the incident light and photoconversion cross-sections (which predict the likelihood of photon absorbance and subsequent phytochrome conversion) for P r and P fr at each wavelength [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, a metric called phytochrome photoequilibrium (PPE) has been used to predict phytochrome-mediated developmental responses [2]. PPE is an estimate of the fraction of active P fr to the total phytochrome pool, and it is calculated from the spectral photon distribution (SPD) of the incident light and photoconversion cross-sections (which predict the likelihood of photon absorbance and subsequent phytochrome conversion) for P r and P fr at each wavelength [2][3][4][5][6][7][8]. Photoconversion cross-sections are closely related to absorption spectra and, when multiplied by the photon intensity at specific wavelengths, they provide an estimate of the rates of conversion between the two forms of phytochrome [3,4].…”
Section: Introductionmentioning
confidence: 99%